2014
DOI: 10.1159/000357064
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin May Be Increased in Newly Diagnosed Celiac Children and Adolescents and Decreases after 6 Months of Gluten-Free Diet

Abstract: Background/Aims: Prolactin (PRL) is produced by the anterior pituitary gland. It exerts its role on the breast gland but also plays a modulatory role in autoimmune mechanisms. Celiac disease (CD) is a gluten-sensitive autoimmune enteropathy sometimes associated with autoimmune endocrinopathies. No data on PRL levels in CD patients are available at diagnosis, and no conclusive data are reported. Methods: We aimed to evaluate PRL secretion in newly diagnosed CD pediatric patients and, in the case of hyperprolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Significantly higher serum PRL levels in CD patients than in controls, with a reduction after six months of a GFD [30], and serum hyperprolactinemia in patients with active disease but not in treated CD subjects [24,31] point to the direct involvement of PRL in the pathogenesis of CD. This is supported by the fact that it has been shown that elevated serum PRL levels in CD patients correlate with disease activity indicated by the presence of malnutrition and the degree of histological damage of the intestinal mucosa [10].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher serum PRL levels in CD patients than in controls, with a reduction after six months of a GFD [30], and serum hyperprolactinemia in patients with active disease but not in treated CD subjects [24,31] point to the direct involvement of PRL in the pathogenesis of CD. This is supported by the fact that it has been shown that elevated serum PRL levels in CD patients correlate with disease activity indicated by the presence of malnutrition and the degree of histological damage of the intestinal mucosa [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a longitudinal study revealed diminished levels of PRL after 6 months following a gluten-free diet. The evidence of decreasing PRL simultaneously with the decline of anti-transglutaminase antibodies suggests a direct connection with a gluten-free diet and hormone levels ( 112 ).…”
Section: Hyperprolactinemia and Autoimmune Diseasesmentioning
confidence: 99%
“…For example, prolactin is produced by the anterior pituitary gland, may be important in breast glandular development and may play a role in autoimmune regulatory mechanisms. In some studies, prolactin levels were increased in recently diagnosed CD in pediatric patients and these levels decreased over a few months with a gluten-free diet[ 83 , 84 ].…”
Section: Other Endocrine Disordersmentioning
confidence: 99%